Der Islam als Alternative: By Murad Hoffmann. Munich: Eugen Diederichs Verlag, 1992, 214 pp. (American Journal of Islam and Society, 1993)
This small book-Islam as an Alternative-by the German ambassadorto Morocco, which contains an excellent foreword by Annemaria e Schimmel,is remarkable for various reasons. Public interest had alwady been heighteneddue to an earlier television interview with the author which, conducted in avery provocative manner, threw his continued diplomatic appointment intoquestion. However, as German attention turned elsewhere, this issue declinedin importance, making it possible for this very eloquent new Muslim to continuerepresenting his country abroad.Events in the Muslim world, such as the Iranian revolution and the Gulfwar, often result in many misrepresentations of Islam in the Western media.But these same events also engender a never-ending series of invitations forreligious dialogue by people of good will who are trying to understand whatis happening and why Islam seems to spread despite its mainly negativeimage in the eyes of non-Muslims. However, Muslims face a problem here:there are few competent dialogue partners who can present accurately the Islamicside. While representatives of the Catholic and Protestant churches areefficiently trained and very well educated, Muslims in Germany are often unableto express fully and coherently their thoughts in German. They alsousually have not received a proper Islamic education. Even if they enroll ina German university specifically for the purpose of acquiring such an education,they are nonetheless tmined to look at their religion through non-Muslimeyes. And it is these very eyes that most often see Islam as “fundamentalist.,“”belligerent,” and “backward, particularly as far as women are concerned,” toname only the most important misconceptions.Hoffmann’s book is remarkable because it deals with many controversialissues head on, thereby providing handy answers and explanations for thoseinvolved in interfaith dialogue. Many new Muslims may have thought alongthe same lines in these matters, but to be able to present them in a few andabsolutely to-the-point replies is another thing.Here are some of these reizworte (emotive words), in an abbreviatedform, together with what the author has to say about them.Fundamentalism: “Each and every religion or ideology develops on somebasics-called Bible, Gospel or ‘Marx, Engels, and Lenin’-which are considereddefinable, concluded, unchangeable and able to support, that is as fundamentals.The same is true of Islam, the fundamentals of which are the ...